Synthesis of monodisperse iron oxide nanoparticles without surfactants - Yang, X.; Shang, Y.; Li, Y.; Zhai, J.; Foster, Neil; Li, Y.; Zou, D.; Pu, Y. (Hindawi Publishing Corporation, 2014)
© 2014 Xiao-Chen Yang et al. Monodisperse iron oxide nanoparticles could be successfully synthesized with two kinds of precipitants through a precipitation method. As-prepared nanoparticles in the size around 10 nm with regular spherical-like shape were achieved by adjusting pH values. NaOH and NH· H were used as two precipitants for comparison. The average size of nanoparticles with NH· H precipitant got smaller and represented better dispersibility, while nanoparticles with NaOH precipitant represented better magnetic property. This work provided a simple method without using any organic solvents, organic metal salts, or surfactants which could easily obtain monodisperse nanoparticles with tunable morphology.